Improvement of Micro-Hole Processing in SiCf/SiC Ceramic Matrix Composite Using Efficient Two-Step Laser Drilling - Yue Cao; Bin Wang; Zhehang Li; Jiajia Wang; Yinan Xiao; Qingyang Zeng; Xinfeng Wang; Wenwu Zhang; Qunli Zhang; Liyuan Sheng (Micromachines)
SiCf/SiC ceramic matrix composite (CMC), a hard and brittle material, faces significant challenges in efficient and high-quality processing of small-sized shapes. To address these challenges, the nanosecond laser was used to process micro-holes in the SiCf/SiC CMC using a two-step drilling method, including laser pre-drilling in air and laser final-drilling with a water jet. The results of the single-parameter variation and optimized orthogonal experiments reveal that the optimal parameters for laser pre-drilling in air to process micro-holes are as follows: 1000 processing cycles, 0.7 mJ single-pulse energy, −4 mm defocus, 15 kHz pulse-repetition frequency, and 85% overlap rate. With these settings, a micro-hole with an entrance diameter of 343 μm and a taper angle of 1.19° can be processed in 100 s, demonstrating high processing efficiency. However, the entrance region exhibits spattering slags with oxidation, while the sidewall is covered by the recast layer with a wrinkled morphology and attached oxides. These effects are primarily attributed to the presence of oxygen, which enhances processing efficiency but promotes oxidation. For the laser final-drilling with a water jet, the balanced parameters for micro-hole processing are as follows: 2000 processing cycles, 0.6 mJ single-pulse energy, −4 mm defocus, 10 kHz pulse-repetition frequency, 85% overlap rate, and a 4.03 m/s water jet velocity. Using these parameters, the pre-drilled micro-hole can be finally processed in 96 s, yielding an entrance diameter of 423 μm and a taper angle of 0.36°. Due to the effective elimination of spattering slags and oxides by the water jet, the final micro-hole exhibits a clean sidewall with microgrooves, indicating high-quality micro-hole processing. The sidewall morphology could be ascribed to the different physical properties of SiC fiber and matrix, with steam explosion and cavitation erosion. This two-step laser drilling may provide new insights into the high-quality and efficient processing of SiCf/SiC CMC with small-sized holes.